Learning to manage your money - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Christine Tanyi explaining some of the secrets behind the success of CAMCCUL, the co-ordinating body for credit unions in Cameroon